Particleboard from coir pith (Bangladesh Journal of Scientific and Industrial Research, 2016)
This study aimed to find out the feasibility of coir pith as a raw material for particleboard production. Considering particle size, an attempt was taken to produce resin bonded coir pith particleboard and binder-less coir pith particleboard as well. The physical and mechanical properties of the board were examined. The particleboard made from medium size particle showed the best performance in aspect of properties. The particleboards made with 16% Melamine Urea Formaldehyde (MUF) had better product quality than binder-less coir pith board. The MOR, MOE, TS and IB were respectively 24.65, 2398, 22.55 and 1.52 N/mm2. Coir pith board may be a sustainable, cheap and durable building and packaging materials and timber substitute.Bangladesh J. Sci. Ind. Res. 51(3), 239-245, 2016